2017
DOI: 10.3390/min7060086
|View full text |Cite
|
Sign up to set email alerts
|

Coal-Based Reduction and Magnetic Separation Behavior of Low-Grade Vanadium-Titanium Magnetite Pellets

Abstract: Abstract:Coal-based reduction and magnetic separation behavior of low-grade vanadium-titanium magnetite pellets were studied in this paper. It is found that the metallization degree increased obviously with an increase in the temperature from 1100 • C to 1400 • C. The phase composition transformation was specifically analyzed with X-ray diffraction (XRD). The microscopic examination was carried out with scanning electron microscopy (SEM), and the element composition and distribution were detected with energy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…As known to all, high CS of finished pellets primarily relies on solid phase consolidation, then the liquid phase bonding . Figure reveals SEM images of finished LGVTMP with different wt% MgO at 200× and 1000×.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…As known to all, high CS of finished pellets primarily relies on solid phase consolidation, then the liquid phase bonding . Figure reveals SEM images of finished LGVTMP with different wt% MgO at 200× and 1000×.…”
Section: Resultsmentioning
confidence: 84%
“…About this new‐type vanadium‐titanium magnetite, viz. low‐grade vanadium‐titanium magnetite (LGVTM), the previous study mainly focused on the utilization by a non‐blast furnace process . The properties of the vanadium‐titanium magnetite in the blast furnace are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, the direct reduction of VTM concentrates by solid reductants has been widely researched [24][25][26][27]. It was found that the reduction of VTM concentrates was more difficult than magnetite due to the different crystal structures and the presence of titanium.…”
Section: Melting Furnacementioning
confidence: 99%
“…The reduction temperature of chromium oxides is relatively high. The molten chromium dissolves into the molten iron when the reduction of chromium oxide is completed . Hence, the reaction of chromium oxide is expressed by Equation which is calculated from Equation and (10).…”
Section: Thermodynamic Analysismentioning
confidence: 99%
“…The vanadium in CVTM is the trivalent vanadium (V 3+ ) forming a solid solution as vanadium spinel FeV 2 O 4 . The stepwise reduction of the vanadium oxides is as following path: FeV 2 O 4 → V 2 O 3 → VO → V → [V].…”
Section: Thermodynamic Analysismentioning
confidence: 99%